Buckling of thin-walled structural steel flexural members - Nguyen, Thi Bich Ngoc. (2008)
This thesis presents experimental and numerical investigations for flexural members of Z-sections with complex stiffeners. The complex stiffeners of the Z-sections consist of inside and outside angled return lips. The Z-sections are thin-walled steel structural members.